A history of mathematics : an introduction - Katz, Victor Joseph, 1942- (Boston : Addison-Wesley, 2009)
A History of Mathematics, Third Edition, provides students with a solid background in the history of mathematics and focuses on the most important topics for today's elementary, high school, and college curricula. Students will gain a deeper understanding of mathematical concepts in their historical context, and future teachers will find this book a valuable resource in developing lesson plans based on the history of each topic. This book is ideal for a junior or senior level course in the history of mathematics for mathematics majors intending to become teachers.
Includes bibliographical references and index.
Keywords: Mathematics -- History; Wiskunde